Phytocannabinoid-rich galenic preparations for topical administration: extraction and stability testing - Kaczorová, Dominika; Peč, Jaroslav; Béres, Tibor; Štefelová, Nikola; Ćavar Zeljković, Sanja; Trojan, Václav; Janatová, Anežka Kosmáková; Klouček, Pavel; Tarkowski, Petr (Frontiers in Pharmacology, 2023)
Although medical cannabis was legalized in Czechia in 2013 and its use in topical treatments of skin disorders is now allowed, galenic formulations prepared from medical cannabis have not been widely implemented in the Czech healthcare system. One of the main reasons is the lack of a straightforward standardized protocol for their preparation. Cannabinoids, e.g., cannabidiol (CBD) and tetrahydrocannabinol (THC), have been shown to have therapeutic effects on various skin conditions, such as atopic dermatitis, psoriasis, scleroderma, acne and skin pigmentation. Recognizing the potential of dermatological treatment with medical cannabis, the present study aimed to evaluate the extraction capacity of various pharmaceutical bases for cannabinoids and the stability of prepared galenic formulations for dermatological applications with respect to cannabinoid content. The results showed that the stability of cannabinoids in formulations depended on the bases' physical and chemical properties. The highest THC decomposition was observed in cream bases and Vaseline, with estimated percentage loss of total content of up to 5.4% and 5.6% per week, respectively. In contrast, CBD was more stable than THC. Overall, the tested bases were comparably effective in extracting cannabinoids from plant material. However, olive oil and Synderman bases exhibited the highest cannabinoid extraction efficiencies (approximately 70%) and the best storage stabilities in terms of the content of monitored compounds. The proposed preparation protocol is fast and easily implementable in pharmacies and medical facilities.